Effect of Sodium Hypochlorite in Ground Fluorotic Enamel: Shear Bond Strength and Surface Analysis - Roque-Márquez, José Gilberto (2021)
Evaluate the effect on the shear bond strength (SBS) of 5% NaOCl applied after acid etching on ground anterior teeth with fluorosis and analyze the surface with scanning electron microscopy (SEM), also compare fluorotic and healthy ground enamel by atomic force microscopy (AFM) and Vickers microhardness (VM). For the SBS test 30 anterior teeth with moderate and severe fluorosis according Dean index were selected by an examiner previously calibrated with an expert in fluorosis by using the intraclass correlation coefficient (ICC). With the help of a calibrated high speed diamond bur for veneer preparation and a parallel chamfer high speed diamond bur the vestibular face was prepared with a uniform reduction of .3 mm under water cooling. In one half of  the vestibular face of the teeth the conventional adhesive procedure was carried out while in the other half was added an additional step with 5% NaOCl applied for 1 minute and washing after acid etchant. A resin post was adhered in each half and load was applied until fracture. The failure mode was evaluated and a SEM analysis was made. Posteriorly 10 samples of fluorotic and healthy ground enamel were used to measure the nanostructural characteristics by AFM (roughness average and absolute depth profile) and the VM in three operative steps (after ground, after etchant and after deproteinization). The Shapiro-Wilks and Brown-Forsythe methods were used to test the distribution of variables. The Paired Student's t-test was used to compare the differences between mean bond strength (MPa) in the two groups for SBS test. Chi-square analyzes were performed to compare the failure modes between groups. One-way ANOVA analysis and Tukey-Kramer post hoc test were used to compare groups for roughness average, absolute depth profile and Vickers microhardness. A greater SBS (32.17±4.20 MPa) and a surface more homogeneous and less contaminated were observed in the deproteinization subgruoup compared to the conventional subgroup (27.74±4.88 MPa). AFM parameters were greater in fluorosis subgroup than in healthy enamel subgroup. VM was lower in the fluorotic enamel in each operative step in comparation with healthy enamel. The use of 5% NaOCl as a deproteinizing agent after acid etchant in ground fluorotic enamel results in better adhesion, which may imply greater success in adhesive treatments. The ground surface of fluorotic enamel shows higher values of roughness and depth and lower values of VM which proves that there is a more irregular and less hard surface.